2009
DOI: 10.1007/s00774-009-0131-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum homocysteine, folate and vitamin B12 in patients with Paget’s disease of bone: the effect of zoledronic acid

Abstract: High serum homocysteine (HCY) and indirectly deficiency of folate and/or vitamin B(12) stimulate bone resorption and adversely affect collagen cross-linking. The aim of this study was the evaluation of serum levels of HCY, folate and vitamin B(12) in patients with Paget's disease of bone (PDB) and the effect of zoledronic acid (ZOL) on their serum levels. Nine consecutive patients with polyostotic PDB (median age 66 years) received a single 5-mg ZOL infusion. Blood samples for HCY, folate, vitamin B(12), 25-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
2
6
0
1
Order By: Relevance
“…To our knowledge, there are only two studies correlating serum Hcy levels with NAFLD severity, but the results are controversial. Higher Hcy levels in NASH and NAFLD patients have been reported in one study [9], whereas other authors have described lower Hcy levels in NASH patients as compared to steatosis subjects [48]. Both studies agree that the serum Hcy might be a noninvasive biomarker for the assessment of NAFLD [9,48].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…To our knowledge, there are only two studies correlating serum Hcy levels with NAFLD severity, but the results are controversial. Higher Hcy levels in NASH and NAFLD patients have been reported in one study [9], whereas other authors have described lower Hcy levels in NASH patients as compared to steatosis subjects [48]. Both studies agree that the serum Hcy might be a noninvasive biomarker for the assessment of NAFLD [9,48].…”
Section: Discussionsupporting
confidence: 57%
“…Higher Hcy levels in NASH and NAFLD patients have been reported in one study [9], whereas other authors have described lower Hcy levels in NASH patients as compared to steatosis subjects [48]. Both studies agree that the serum Hcy might be a noninvasive biomarker for the assessment of NAFLD [9,48]. Population and methodological differences may account for the contradictory findings in the literature.…”
Section: Discussionmentioning
confidence: 41%
“…Other researchers and we have shown that Hcy increases collagen turnover in various pathological conditions (Miller et al, 2002; Polyzos et al, 2010). Here we report that FA mitigates Hcy induced collagen turn over by decreasing the expression of Col4a and Col1a in the cochlear tissue of CBS+/− mice.…”
Section: Discussionmentioning
confidence: 47%
“…Polyzos et al reported baseline increase in hcy levels in patients with Paget's disease along with a decrease in bone forming markers like bone-specific alkaline phosphatase and serum folate levels. [12] In the present study, in osteosarcoma patients a significant positive correlation was observed between serum folate and hcy levels [r = 0.473, P < 0.01, Figure 1]. Also, a significant negative correlation was observed between Vitamin B 12 and hcy levels in osteosarcoma patients [r = −0.573, P < 0.001, Figure 2].…”
Section: Discussionsupporting
confidence: 49%